The Influence of Financial Innovation, Digital Technology, and Financial Literacy on Financial Inclusion with Fintech as a Moderation Variable in Culinary Entrepreneurs in Bandar Lampung - Erlin Kusnita; Texy Sagara; Elsa Silviana; Alfira Dewi Rohmah; Rike Oktavianika; Veni Hermawati (Prosiding International conference on Information Technology and Business (ICITB), 2022)
The phenomenon in Bandar Lampung found that culinary businesses still have obstacles with a very limited ability to access financial information in financial institutions. In addition, low ability and knowledge of human resources, simple management and financial reporting that is not in accordance with accounting standards, and the limited use of technology are also obstacles in the development of medium-sized enterprises. This study aimed to determine the influence of financial innovation, technology, and financial literacy on financial inclusion and to find out the influence of financial innovation, digital technology, and financial literacy on financial inclusion with Fintech as moderation in culinary entrepreneurs in Bandar Lampung City This type of research was quantitative research using questionnaire data collection techniques. Data analysis in this study used normality test methods, linearity tests, and hypothesis tests.Keywords--- Financial Innovation, Digital Technology, Financial Literacy, Financial Inclusion, Fintech